Characterisation and quantification of protein oxidative modifications and amino acid racemisation in powdered infant milk formula. (2nd January 2019) - Chen, Zhifei; Leinisch, Fabian; Greco, Ines; Zhang, Wei; Shu, Nan; Chuang, Christine Y.; Lund, Marianne N.; Davies, Michael J.
Abstract: Modification of proteins in infant milk formula (IF) is of major concern to the dairy industry and consumers. Thermal treatment is required for microbiological safety, but heat, light, metal-ions and other factors may induce oxidative damage, and be a health risk. In this study protein modifications in IFs were quantified. IFs contained both reducible (disulphide) and non-reducible (di-tyrosine, lanthionine, lysinoalanine) protein cross-links. Dehydroalanine and the cross-linked species lanthionine and lysinoalanine were detected. Protein carbonyls were detected predominantly on high molecular mass materials. Oxidation products of phenylalanine ( m -tyrosine), tryptophan ( N -formylkynurenine, kynurenine, 3-hydroxykynurenine), tyrosine (di-tyrosine) and methionine (methionine sulphoxide) were detected, consistent with amino acid modification. Higher levels of most of the markers of protein modification were present in the hydrolysed protein brand, when compared to the conventional IF samples, indicative of increased damage during additional processing. Significant levels of racemised (D-) amino acids were present. These data indicate that amino acids in proteins in IFs are modified to a significant extent during manufacture, with hydrolysed IF being particularly prone.